Role of macrophages in chronic kidney disease - JIANG Ya-li; LIU Xiao-wei (Linchuang shenzangbing zazhi)
Chronic kidney disease（CKD） has become a major health problem worldwide.This review describes the role of macrophages in CKD and highlights the importance of anti-inflammatory M2 macrophage activation in both renal fibrosis and wound healing processes.Furthermore,the mechanisms by which M2 macrophages induce renal repair and regeneration are still under debate and currently demand more attention.The M1/M2 macrophage balance is closely related to the renal microenvironment and could influence CKD progression.In fact,renal microenvironment and M2 macrophage plasticity can be the major hurdles for establishing macrophage cell-based therapies in CKD.M2 macrophage-based therapy will be promising if the M2 phenotype remains stable in vitro.However,a greater understanding of phenotype polarization is still required.Moreover,better strategies and targets to induce macrophages polarization in vivo should guide future investigations in order to abate kidney diseases.